Prevalence of Listeria monocytogenes infection in women with spontaneous abortion, normal delivery, fertile and infertile - Amjad Ahmadi; Rashid Ramazanzadeh; Safoura Derakhshan; Mazaher Khodabandehloo; Fariba Farhadifar; Daem Roshani; Atefeh Mousavi; Manouchehr Ahmadi Hedayati; Mohammad Taheri (BMC, 2022)
Abstract Background Listeria monocytogenes with a vast range of natural reservoirs is more known for being a food-borne pathogen. Human infections have shown an impact on pregnancy outcomes, so, this study surveyed the frequency of L. monocytogenes infection involving different groups of women. Methods This study enrolled a total sample consisting of 109 women with spontaneous abortion, 109 women with normal delivery, 100 fertile women, and 99 infertile women aged 19-40 years and willing to participate in the study. The research tool in this study was a questionnaire and Polymerase chain reaction (PCR) test. Results According to the results, the frequency of L. monocytogenes infection was 4/109 (3.66%) observed among women with spontaneous abortion, 2/109 (1.83%) among women with normal delivery, 3/100 (3%) among fertile women, and 0/99 (0%) among infertile women. Conclusion There was no significant relationship between Listeria monocytogenes infection and pregnancy outcomes of spontaneous abortion and infertility.